Regulatory elements in tetracycline-encoding gene clusters : the otcG gene positively regulates the production of oxytetracycline in Streptomyces rimosus - Lešnik, Urška (Array, 2009)
Summary: The expression of bacterial polyketide synthase gene clusters is often controlled by a number of different families of regulatory proteins that can have either a pathway-specific or a pleiotropic mode of action, e.g. the SARP family (Streptomyces antibiotic regulatory proteins), ribosome-associated ppGpp synthetase, γ-butyrolactone-binding regulatory proteins, and two-component regulatory proteins. The molecular genetics of such regulatory mechanisms that govern the biosynthesis of tetracyclines is poorly understood. In this work, a comparative bioinformatic analysis of regulatory genes present in three tetracycline antibiotic gene clusters, namely oxytetracycline (OTC), chlortetracycline and recently cloned chelocardin gene clusters of S. rimosus, S. aureofaciens and Amycolatopsis sulphurea has been performed. A SARP family regulatory protein is located in the chlortetracycline gene cluster, but is not detected in the gene cluster encoding OTC biosynthesis. Interestingly, the only regulatory element identified in chelocardin gene cluster was chdA, an otrR and ctcR homologue from the TetR family of regulators that regulates the expression of the otrB and ctc05 exporter genes in the oxytetracycline and chlortetracycline gene clusters. In the oxytetracycline gene cluster, a new LAL (LuxR) family regulatory gene homologue, otcG, was identified. This homologue is also present in the ctc gene cluster. By gene disruption and overexpression experiments, a 'conditionally positive' role of otcG in OTC biosynthesis has been demonstrated. The observation, the bioinformatics data and the previous work on phosphate regulation suggest the presence of a more complex, fine tuning role of the otcG gene product in overall expression of genes for OTC biosynthesis